Students' Experiences with English Movies for Vocabulary Development and Motivation Based on Learning Style - Pratama, Yoga; Rizky Pratiwi, Widya; Saehu, Andang (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
Vocabulary is fundamental to English language proficiency, yet teaching it remains challenging due to limited instructional time and the complexity of word associations. While various methods have been employed to support vocabulary learning, few studies have explored the impact of English movies on vocabulary mastery and student motivation in relation to learning styles. This study addresses that gap by examining how English movies support vocabulary acquisition and motivation among students with diverse learning preferences at Junior High School 3 Terusan Nunyai. Using a qualitative case study design, data were collected through interviews, observations, and documentation, with purposive sampling involving school leaders, teachers, and selected students. A learning style inventory identified visual learners as the majority. The findings indicate that English movies enhance vocabulary retention and motivation, especially for visual and auditory learners, and can also engage kinesthetic learners when combined with interactive classroom activities. The use of movies provides authentic, contextual, and multisensory experiences that enrich learning and increase student engagement. The study concludes that integrating English movies into English instruction is an effective strategy to improve vocabulary mastery and student motivation, offering valuable insights for teachers and contributing to more inclusive and engaging learning environments.